Орлиця ("шістдесятниці" Лідії Орел - 70) - Яременко, В. (Народна творчість та етнографія, 2007)
The article is dedicated to the life and activity of famous scientist, ethnographer, folklorist and public figure Lidiya Orel. The author declared many-sided and entire character of this brilliant person, which helped her to hold out in conditions of pursuits under totalitarianism. She is wellknown ethnographer and expert of museums among cultural figures both in Motherland and abroad.